2022
DOI: 10.55730/1300-0527.3306
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of fluorescence and metal interaction properties of racemic 7,8,9,10-tetrahydro-3-hydroxy-4-(1-hydroxyethyl)benzo[c]chromen-6-one

Abstract: The design or investigation of fluorescence probes continues to receive attention with respect to the diverse applications of spectrofluorometry. Depending on the highly sensitive character, fluorescence spectroscopy-based methodologies have been widely used in recent years in different sciences, including analytical, environmental, and medicinal chemistry areas. In our previous works, we have shown the iron (III) selective on-off sensor properties of benzo[c]chromen-6-one derivatives. In this study, we have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Accordingly, the linearity for each title molecule with the developed fluorescence detection was established with the coefficient of determination obtained (i.e., each was higher than 0.9990). It is of significance to also state that depending on the substituent effect on benzo[c]chromen-6-one system, the general fluorescence intensities obtained for Urolithin A and B were found higher in comparison to the fluorescence intensities obtained for their methyl ether derivatives which were in parallel with our previous observations [12][13]21]. The specificity studies apparently displayed the visual priority for the fluorescence detectors over DAD detectors.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Accordingly, the linearity for each title molecule with the developed fluorescence detection was established with the coefficient of determination obtained (i.e., each was higher than 0.9990). It is of significance to also state that depending on the substituent effect on benzo[c]chromen-6-one system, the general fluorescence intensities obtained for Urolithin A and B were found higher in comparison to the fluorescence intensities obtained for their methyl ether derivatives which were in parallel with our previous observations [12][13]21]. The specificity studies apparently displayed the visual priority for the fluorescence detectors over DAD detectors.…”
Section: Resultssupporting
confidence: 78%
“…Indeed, the LOD and LOQs obtained were all found less than the ones for pure UV detection. Previous studies indicated the concentrations of diverse urolithins in plasma can reach up to 100µM levels upon exposure to an ellagitannin-rich diet [14][15][16][17][18][19][20][21][22][23][24][25][26]. The LOD and LOQ concentrations via the fluorescence technique displayed in this research study pointed out the very low nanomolar levels that can be either detected or quantified.…”
Section: Discussionmentioning
confidence: 53%